Personal traits of women and their educational applications - Mandahawi, Hamzeh Mohammad (Journal of Educational and Psychological Sciences, 2025)
The research aims to explain women’s personality traits and their educational applications. For this reason, the researcher studied the concept of women’s personality traits by referring to linguistic dictionaries and devising educational applications for women’s personality traits. The nature of the research required that I adopt the analytical, deductive and descriptive approach, and among the most prominent results that the researcher reached was defining the personal characteristics of a woman as the qualities that characterize a woman that distinguish her from other members of her gender in many characteristics, and were formed as a result of her interaction with the surrounding environment or were formed by the action of The genetic factor or the result of her social upbringing, and the behaviors that result from this interaction regulate her relationship with the Creator, with herself, and with people, in order to obtain God’s pleasure. In the field of educational institutions, women were characterized by positive traits, including: a strong personality and fairness in treatment, Among the characteristics of women in the field of advocacy are sincerity, concern for advocacy, legal and advocacy knowledge, understanding people’s natures, customs and traditions, excellence and superiority, reason and balance, innovation and innovation. The study recommended integrating women’s personal characteristics into educational programs, both in general and higher education, to enhance the effectiveness of the educational process. Teachers and educators should also be directed to use teaching methods that take into account individual differences among female students, particularly with regard to their psychological and personal characteristics.